Self-instruction checklists and addition skills of students with mild mental retardation - Mina, Jennilyn Grace C.
The study focused on the use of self-instruction checklists as a metacognitive approach in teaching students with mild mental retardation. Participants included 5 mainstreamed, third-grade students from Batino Elementary School. The study lasted for a month, including the pretesting and posttesting. Results of the study showed that self-instruction checklists increased the metacognitive skills of the students and improved their performance in solving addition with regrouping. This study recommends the metacognitive scaffolding as an instructional method in teaching students with mild mental retardation in the area of problem solving.